Electrochemomechanical Fatigue: Decoupling Mechanisms of Fracture-Induced Performance Degradation in LiXMn2O4. Issue 11 (11th August 2018) - McGrogan, Frank P.; Raja, Shilpa N.; Chiang, Yet-Ming; Van Vliet, Krystyn J.
Abstract : Decades of Li-ion battery (LIB) research have identified mechanical and chemical culprits that limit operational lifetime of LIB electrodes. For example, severe capacity fade of unmodified LiX Mn2 O4 electrodes has been linked historically with Mn dissolution and, more recently, fracture of the electrochemically active particles. Mitigation approaches targeting both effects have prolonged cycle and calendar life, but the fundamental mechanistic sequences linking fracture to capacity fade in LiX Mn2 O4 and many other cathode materials remain ambiguous. Here, we investigate specifically the temporal correlations of fracture, capacity fade, and impedance growth to gain understanding of the interplay between these phenomena and the time scales over which they occur. By conducting controlled excursions into the cubic-tetragonal phase transformation regime of LiX Mn2 O4, we find that fracture contributes to impedance growth and capacity fade by two distinct mechanisms occurring over different time scales: (1) poorly conducting crack surfaces immediately hinder electronic conduction through the bulk of the electrode, and (2) capacity fades at a faster rate over multiple cycles, due plausibly to dissolution reactions occurring at newly formed electrode-electrolyte interfaces. The deconvolution of these effects in a well-studied cathode material such as LiX Mn2 O4 facilitates understanding of the complex relationship between mechanics and electrochemistry in LIB electrodes.